KEJADIAN ANKILOSTOMIASIS DI YOGYAKARTA BERDASARKAN JENIS PAKAN KUCING - , VINCENT ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Ancylostomiasis is a parasitic infection in gastrointestinal tract of cats. This infection occurs in a raw or commercial food. The purpose of this research is to determine ancylostomiasis rates in Yogyakarta according to feeding variations. A total of 280 fecal samples grouped by feeding variations (commercial, mix, and non-commercial). Samples were analyzed by native and centrifuged tests. Native test performed by diluting the feces with water then smear. The rest of dilution were centrifuged twice then added saturated salt or sugar until the cylinder nearly full. Based on test numbers of helminth eggs were counted. Based on test positive results a total: 5 of 183 (2,73%), 9 of 75 (12%), 6 of 22 (27,27%) for ancylostomiasis were respectively fed with commercial, mixed, and non-commercial. The result showed that ancylostomiasis was lower in cats with commercial food (2,73%) than mix (12%) or non-commercial food (27,27%). Key words: ancylostoma, cat, infection, Yogyakarta